The Influence of Raw Material Supply Chain Management on the Performance of Sugar Palm SMEs at CV. Mitra Mandala - Rizkiansyah, Aldi; Aliudin, Aliudin; Sariyoga, Setiawan (Dinasti Publisher, 2025)
This study aims to determine the influence of supply chain management consisting of information sharing, trust, long-term relationships and collaboration on the performance of Mitra Mandala companies. This research was carried out for three months from November to December 2024. This study is of a quantitative descriptive type using multiple linear regression analysis. The sampling technique used in this study was purposive sampling and obtained as many as 64 respondents. The results of this research show that information sharing has a positive but not significant effect on the company's performance with a score of 1,056 < 2,001. The confidence variable had a positive but not significant effect on performance with a value of 1.665 < 2.001. The long-term relationship variable had a positive but insignificant effect with a value of 0.616 < 2.001. The collaboration variable had a positive and significant influence on performance with a score of 7,700 > 2,001.